Accurate identification of melanoma tumor margins: a review of the literature. (August 2012) - Danialan, Richard; Gopinath, Arun; Phelps, Amanda; Murphy, Michael; Grant-Kels, Jane M
More than 8000 people die of melanoma in the USA annually. Although early detection of melanoma results in a 5-year survival of up to 90–95%, those presenting at advanced stages have dismal prognoses due to ineffective systemic therapies. In general, patients with early melanoma can be successfully treated with local surgery. However, approximately 8–20% of lentigo maligna melanomas recur, leading to frequent re-excisions, cosmetic issues and, as a result, increased medical costs. An accurate evaluation of melanoma margins is important to prevent local tumor recurrence and progression to advanced stage disease. This review will discuss the role of clinically based noninvasive tools, histology, immunohistochemistry and molecular technologies in melanoma margin assessment.